2019
DOI: 10.1007/s40123-019-00214-z
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Second-Generation Trabecular Micro-Bypass Stents (iStent Inject) Implantation with Cataract Surgery in Different Glaucoma Subtypes and Severities

Abstract: Purpose: To assess the 1-year efficacy and safety of the implantation of two second-generation trabecular micro-bypass stents (iStent Inject Ò) with concomitant cataract surgery in various subtypes and severities of glaucoma. Methods: This single-surgeon, consecutive case series from a Canadian academic ophthalmology center included subjects with cataract, glaucoma, and the need to reduce intraocular pressure (IOP) and/or medications. The 12-month outcomes included mean IOP and medication burden as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…The IOP and medication reductions and favorable safety observed in this study are consistent with existing literature on iStent inject, which includes studies of standalone and cataract-combination procedures, different subtypes and severities of glaucoma, and different study designs [30][31][32][33][34][35][36][37][38][39][40][41][42]. A large multicenter pooled analysis showed 12-month outcomes of iStent inject implantation with cataract surgery in various types of glaucoma as well as ocular hypertension.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The IOP and medication reductions and favorable safety observed in this study are consistent with existing literature on iStent inject, which includes studies of standalone and cataract-combination procedures, different subtypes and severities of glaucoma, and different study designs [30][31][32][33][34][35][36][37][38][39][40][41][42]. A large multicenter pooled analysis showed 12-month outcomes of iStent inject implantation with cataract surgery in various types of glaucoma as well as ocular hypertension.…”
Section: Discussionsupporting
confidence: 83%
“…In three independent single-surgeon studies with different baseline patient populations, significant IOP and medication reductions were demonstrated following iStent inject with cataract surgery. An Australian case series showed 29.4% IOP reduction and 94.7% medication reduction [41]; a Brazilian case series showed 19.1% IOP reduction and 94.1% medication reduction [33]; and a Canadian study showed 17.8% IOP reduction and 56% medication reduction [42]. In a 3-year prospective case series of patients undergoing iStent inject implantation with cataract surgery in Germany, IOP reduced by 37% (from 22.6 mmHg to 14.3 mmHg) and medications reduced by 68% (a 1.7-medication reduction) [39], with similarly favorable IOP and medication outcomes achieved in POAG and PXG subgroups.…”
Section: Discussionmentioning
confidence: 94%
“…Two of those implants, i.e., the iStent®, which consists of heparin-coated nonferromagnetic titanium, and the Hydrus TM , made of nitinol (nickel-titanium alloy), are metal based. The medical-grade titanium is described as biocompatible with the eyes, with no foreign body reaction after iStent® implantation [12]. Titanium is widely used in bone surgery or dental implants, whereas titanium is no longer seen as “inert” but induces a foreign body reaction that allows osseointegration of the foreign body as a healing process – its long term result is seen as dependent on a “foreign body equilibrium” [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…1a) is a 12-item subjective questionnaire designed to assess a patient's symptoms related to chronic dry eye, its severity, and its impact on ability to function [32]. OSDI scores range from 0 to 100, with severity defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and severe (33-100). The Oxford Schema (Fig.…”
Section: Osd Testing Protocolsmentioning
confidence: 99%
“…Both micro-scale devices are designed to create a patent pathway through the diseased trabecular meshwork into Schlemm's canal, thereby increasing aqueous humor outflow from the anterior chamber and decreasing intraocular pressure (IOP). Stent implantation has been examined in the setting of cataract surgery or as a standalone procedure, in varying glaucoma severities ranging from glaucoma suspect to refractory glaucoma, and in various glaucoma subtypes (e.g., pseudoexfoliative, pigmentary, normal-tension) as well as in primary open-angle glaucoma (POAG) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In both long-and short-term followup, stent implantation has consistently demonstrated substantial reductions in IOP and medication burden.…”
Section: Introductionmentioning
confidence: 99%